2017
DOI: 10.1016/j.pacs.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Fluence compensation in raster-scan optoacoustic angiography

Abstract: Modern optical imaging techniques demonstrate significant potential for high resolution in vivo angiography. Optoacoustic angiography benefits from higher imaging depth as compared to pure optical modalities. However, strong attenuation of optoacoustic signal with depth provides serious challenges for adequate 3D vessel net mapping, and proper compensation for fluence distribution within biotissues is required. We report on the novel approach allowing to estimate effective in-depth fluence profiles for optoaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
(35 reference statements)
0
20
0
Order By: Relevance
“…When the sphere was uniformly illuminated, its entire surface became visible with the reconstructed images, accurately resembling the theoretically predicted (simulated) values. Even though it has been shown that OA images can, in principle, be corrected for nonuniform illumination and light attenuation, it was not necessary in this case . Such correction for limited‐view conditions or for a relatively low number of measuring positions can be still hampered by streak‐type artifacts associated with strong nonuniformity of the excitation light field (hot spots) .…”
Section: Discussionmentioning
confidence: 99%
“…When the sphere was uniformly illuminated, its entire surface became visible with the reconstructed images, accurately resembling the theoretically predicted (simulated) values. Even though it has been shown that OA images can, in principle, be corrected for nonuniform illumination and light attenuation, it was not necessary in this case . Such correction for limited‐view conditions or for a relatively low number of measuring positions can be still hampered by streak‐type artifacts associated with strong nonuniformity of the excitation light field (hot spots) .…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, the current fast-sweep PAUS system can be programmed to interleave US images at frame rates greater than the 50 Hz PA frame rate. ) [34][35][36][37][38][39][40][41][42][43]. They can be estimated ex vivo or even in vivo but require additional equipment and significant measurement time not compatible with real-time imaging [33,34,40,43,70].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this requires a precise map of tissue optical properties, which cannot be measured or calculated during imaging. Several methods have attempted to estimate and compensate fluence variations [34][35][36][37][38][39][40][41][42][43], but none work well clinically where real-time or near real-time corrections are needed. In most cases, fluence is compensated using an approximate exponential function equalizing intensities.…”
Section: Mainmentioning
confidence: 99%
“…14 In this paper, we report a reconstruction algorithm comprising improved SAFT algorithm 1,11,15,16 accounting for both the spatial response 17 of the acoustic antenna 10 and the spatial distribution of optical fluence. 14,18 For precise calculation of rapid in-depth attenuation of probing laser radiation, we employ 3-D Monte Carlo code previously customized for simulation of the complex geometry of AR-PAM light illumination in medium with optical properties typical for biotissues. 14 At the first step, the SAFT procedure with account for antenna spatial response (ASR) is performed.…”
Section: Introductionmentioning
confidence: 99%
“…14,18 For precise calculation of rapid in-depth attenuation of probing laser radiation, we employ 3-D Monte Carlo code previously customized for simulation of the complex geometry of AR-PAM light illumination in medium with optical properties typical for biotissues. 14 At the first step, the SAFT procedure with account for antenna spatial response (ASR) is performed. Accurate account for the ASR is considered along with the proposed simplified approach allowing for significant speedup in processing.…”
Section: Introductionmentioning
confidence: 99%